Generics: Java vs. C++ - Khalifa, Ahmed (2005)
Jyväskylä: University of Jyväskylä, 2005. 28 p. Bachelorʹs Thesis Generic programming is a widely appreciated and strongly affecting paradigm in software development. A number of programming languages now support generic programming, such as C++, Ada, and Haskell. Generics are the most recent enhancement to the type system of the Java programming language. This advanced feature of Java 1.5 is most notably similar to templates in C++, as some might like to claim. Templating, genericity, parameterized types, or parametric polymorphism refer to the same technique; basically, instantiating versions of classes using some type as a parameter, such as integer, float, or a class. This thesis work gives a comparison of generics in C++ against the newly introduced genericity extension to the Java programming language.